PERTANGGUNGJAWABAN HUKUM PENCANTUMAN KONTAK DARURAT DALAM PERJANJIAN PINJAMAN ONLINE LEGAL LIABILITY INCLUSION OF EMERGENCY CONTACTS IN ONLINE LOAN AGREEMENTS - Ika Octavia Vidianingrum Hariyanto; Ahmad Sholikhin Ruslie (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Personal data is data about a person's origin, name, age, gender, education, occupation, address, and position in the family. Not long ago, an online loan application appeared where the provider could access the borrower's contact details, namely by contacting all the borrower's contacts and notifying that the borrower was in debt outside the emergency contact. This is misuse of personal data. In accordance with Law Number 23 of 2006 concerning Population Management, personal data of residents must be protected and the Decree of the Minister of Communication and Information Technology Number 20 of 2016 concerning Protection of Personal Data in Electronic Systems is explained. Stating that you must maintain the confidentiality of personal data and protect data from the beginning of collection. The purpose of this research is to find out what the legal relationship between online lenders and partners who are used as emergency contacts are and what are the legal implications of implementing emergency contacts for online loans for the parties. The type of research used is normative legal research with a legal approach and a conceptual approach. The legal materials used consist of primary legal materials and secondary legal materials. The technique of collecting legal materials is done through the use of library research techniques. The analytical technique used in this research is descriptive method. Based on these conclusions, the results of this study are that it is illegal for borrowers to misuse personal data in the form of third party numbers as emergency contacts, and it is recommended that: 1); Regulations on the protection of emergency contacts should pay more attention to third party P2P lending practices in Indonesia; 2) Government In practice in Indonesia, fintech must be monitored in detail; 3) The Financial Services Authority must establish a special APS institution to resolve online fintech business disputes